Preparation of Metallic Nanoparticles - Michalcova, Alena; Vojtech, Dalibor; Marek, Ivo; Svobodova, Petra; Novakova, Radka (Manufacturing Technology Journal, 2013)
Nanomaterials are substances with high application potential. It this article, the preparation technique are reviewed with aiming on selective leaching method. This method is based on preparation of conviniet binary alloy in form of supersaturated solid solution and consequent matrix dissolution. In the same time, the minor element forms nanoparticles. The need of rapid solidification of binary precursor before leaching is explained. Nanoparticles from Ni and Ag prepared by selective leaching form AlNi20 and MgAg10 alloys, were characterized by X-ray diffraction and by electron microscopy (SEM and TEM).
Keywords: nanomaterials; metallic nanoparticles; selective leaching